A fluorescence color card for point-of-care testing (POCT) and its application in simultaneous detection. Issue 16 (27th July 2021) - Lu, Fan; Yang, Sisi; Ning, Yu; Wang, Fubing; Ji, Xinghu; He, Zhike
Abstract : A novel strategy for the POCT of glucose and the simultaneous detection of multiple targets using different fluorescence color cards is developed. Abstract : Diabetes mellitus has received much attention because its complications include liver, kidney, eye, heart and cerebrovascular diseases. Thus, it would be highly significant to develop a rapid and efficient method for glucose detection in biological samples. In this work, a point-of-care testing (POCT) method of glucose detection was proposed using a standard colorimetric card for semi-quantitative determination patterns. In the prepared fluorescence color card for glucose, a good linear relationship was acquired by plotting the ratio of the grayscale value ( I / I 0 ) versus the logarithm of glucose concentration within 100.0 to 1000.0 μmol L −1, and the LOD of glucose detection was 1.1 μmol L −1 . A large number of actual samples (30 serum and 7 urine) were analyzed and the results demonstrated that this method had good potential to be applied in the primary screening of diabetic patients. In addition, this method is universal and can be applied in the simultaneous detection of multiple small molecules. It provides a new strategy for the primary screening of multiple diseases simultaneously, which presents excellent application potential.